Environmental and economic determinants of temporal dynamics of the ruminant movement network of Senegal - Katherin Michelle García García; Andrea Apolloni; Alessandra Giacomini; Mamadou Ciss; Mathioro Fall; Adji Marème Gaye; Elena Arsevska; Asma Mesdour; Etienne Chevanne; Fabrizio Rosso; Eric Cardinale; Cécile Squarzoni Diaw; et al. (Scientific Reports, 2023)
Abstract Our understanding of the drivers of the temporal dynamics of livestock mobility networks is currently limited, despite their significant implications for the surveillance and control of infectious diseases. We analyzed the effect of time-varying environmental and economic variables—biomass production, rainfall, livestock market prices, and religious calendar on long-distance movements of cattle and small ruminant herds in Senegal in the years 2014 and 2019. We used principal component analysis to explore the variation of the hypothesized explanatory variables in space and time and a generalized additive modelling approach to assess the effect of those variables on the likelihood of herd movement between pairs of administrative units. Contrary to environmental variables, the patterns of variation of market prices show significant differences across locations. The explanatory variables at origin had the highest contribution to the model deviance reduction. Biomass production and rainfall were found to affect the likelihood of herd movement for both species on at least 1 year. Market price at origin had a strong and consistent effect on the departure of small ruminant herds. Our study shows the potential benefits of regular monitoring of market prices for future efforts at forecasting livestock movements and associated sanitary risks.